Identifying Causal Factors of Child Marriage in Sumenep - Madura - Rusmilawati Windari; Tolib Effendi (Technium Social Sciences Journal, 2023)
Child marriage is a global social phenomenon that has even been identified as a crucial issue of child protection in the 21st century and has been addressed by various countries in Eastern Europe, Africa, and Asia. Indonesia itself has declared a child marriage emergency because by 2020 it was included in the 10 countries with the highest number of child marriages in the world, ie, about 1,220,900 children with early marriages were scattered in 22 provinces, one of which is East Java with 6084 cases in 2020, with the largest percentage in Madura Island and one in Sumenep Island with a total of 1723 cases. The Havana Convention of 1990 states that the elimination of the causal factors of social problems in a society is the most effective means of addressing the social problems themselves and must be an integral part of social defense itself. This paper is driven to identify and analyze the determinant causal factors of child marriage in Sumenep. It is written based on empirical legal research with a socio-legal approach, which prioritizes primary data obtained from the results of interviews and questionnaires and is analyzed descriptively and qualitatively. The results show that the causal factors of child marriages in Sumenep are dominated by cultural practices such as the “tan-pangantanan ” tradition, which is also promoted by the government as part of the preservation of local traditions, the conceptual shift of ’ Tompangan ’ Tradition, excessive fanaticism toward Muslim Priests (Kyai), low education, economic gain, and the worriness of free sex.